2013
DOI: 10.1002/adfm.201300709
|View full text |Cite
|
Sign up to set email alerts
|

Femto‐Second Laser‐Based Free Writing of 3D Protein Microstructures and Micropatterns with Sub‐Micrometer Features: A Study on Voxels, Porosity, and Cytocompatibility

Abstract: Femto‐second laser‐based free‐writing of complex protein microstructures and micropatterns, with sub‐micrometer features and controllability over voxel dimension, morphology, and porosity, is reported. Protein voxels including lines, spots, and micropillars are fabricated. Laser power, exposure time, z‐position, protein and photosensitizer concentrations, but not scanning speed, are important controlling parameters. A lateral fabrication resolution of ≈200 nm is demonstrated in 2D line voxels. 3D spot voxels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…The fabrication of (sub)micrometer‐sized 3D shape‐shifting structures remain a challenge due to the difficulties and lack of fabrication tools for the precise fabrication and positioning of structures. Photo­lithography emerges as a promising technique for the fabrication of defined, 3D polymeric microstructures . Using a masked‐directed multiphoton lithography, pH‐responsive bovine serum albumin (BSA) protein microstructures with differing cross‐linking densities that qualitatively curl to different extents in response to pH change have been fabricated .…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of (sub)micrometer‐sized 3D shape‐shifting structures remain a challenge due to the difficulties and lack of fabrication tools for the precise fabrication and positioning of structures. Photo­lithography emerges as a promising technique for the fabrication of defined, 3D polymeric microstructures . Using a masked‐directed multiphoton lithography, pH‐responsive bovine serum albumin (BSA) protein microstructures with differing cross‐linking densities that qualitatively curl to different extents in response to pH change have been fabricated .…”
Section: Introductionmentioning
confidence: 99%
“…However, after photostructuring by TPS, most of them involve multistep processes such as phase inversion or thermal annealing to achieve the desired properties . In this regard, only few works have been focused on the development of directly crosslinkable functional materials suitable for TPS . Indeed, this field of research is still very challenging because it is usually rather difficult to combine antagonist parameters to ensure both integrity and specific properties of the functional material during the processing route.…”
mentioning
confidence: 99%
“…The orthogonal views of the ECM/BSA microstructures revealed that a thin layer of ECM protein was crosslinked to the top surface of the prefabricated BSA micromatrix. Instead of mixing and co‐crosslinking both BSA and ECM proteins to form the ECM–containing 3D protein microstructures and micropatterns, as we described in a previous study,[14b] here we crosslinked the ECM proteins at the solid–water interface between the BSA protein microstructures and the ECM protein solutions. By crosslinking the ECM proteins to form a very thin layer at the water–solid interface between the BSA protein microstructures and the ECM solution, we minimized the influence of the ECM crosslinking on the intrinsic material property elastic modulus of the BSA micromatrix, and thus we effectively decoupled these two properties.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the noncontact laser‐based crosslinking makes it possible to functionalize the surface of extremely soft 3D microstructures at selected locations with specific densities without damaging their topological features. Previous studies demonstrated the ability of two‐photon microfabrication to fabricate complex protein micropatterns with precisely controlled voxels, topological structures and porosity, as well as mechanical properties . The ECM niche is one of the most important components of cell niche, and thus plays a critical role in cell–matrix interactions.…”
Section: Introductionmentioning
confidence: 99%